Telerehabilitation for Geriatric with Dementia and Long Covid-19 - Melinda Harini; Ika Fitriana; Satyanaya Widyaningrum; Deddy Tedjasukmana; Yunisa Trivarsary; Intan Savitri; Siti Dwi Astuti (Faculty of Medicine, Universitas Airlangga, 2024)
Rehabilitation is crucial for individuals who have survived COVID-19, particularly those who are older and have pre-existing health conditions. These survivors may experience long covid symptoms up to four months after infection. Elderly individuals suffering from long covid face difficulties in undergoing conventional rehabilitation methods due to limitations in mobility, lack of social interaction, and inadequate healthcare accessibility. As a result, telerehabilitation has arisen as an alternate form of care. This case report intends to present empirical evidence on the enhancement of functional status in a geriatric long covid patient following telerehabilitation. We present a case of an elderly woman with underlying dementia who developed long covid. The symptoms included of dyspnea and mobility impairment. We provide a telerehabilitation program for three weeks with an active-assisted range of motion exercises. Following three sessions of telerehabilitation, we could see improvement in her Physical Mobility Scale (PMS). After 20 days, the patient's PMS score increased by 3 points.